2005
DOI: 10.1021/ma050061n
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Melts:  Polymer Chains at the Air−Water Interface

Abstract: Both physical surface rheology and computer simulation experiments were performed to understand the conformation of polymers in 2D systems. The interfacial stress rheometer was used to measure surface rheological properties of Langmuir monolayers of poly(tert-butyl methacrylate) with molecular weights between 81.5 and 780 kg mol-1. The Π−A isotherms for these monolayers show two transitions:  a plateau at Π ≈ 18 mN m-1 and a bend at Π ≈ 52 mN m-1. The properties of the films are shown to be substantially diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 26 publications
7
55
1
Order By: Relevance
“…9), becoming near-reversible at the compressed state u ∼ u 0 . In any case, it must be considered that the above qualitative explanation may not be unique [32,38], and that the present data do not constitute a rigorous proof of it.…”
Section: Stress-strain Curves In the Concentrated Regime: Elastoplastmentioning
confidence: 78%
“…9), becoming near-reversible at the compressed state u ∼ u 0 . In any case, it must be considered that the above qualitative explanation may not be unique [32,38], and that the present data do not constitute a rigorous proof of it.…”
Section: Stress-strain Curves In the Concentrated Regime: Elastoplastmentioning
confidence: 78%
“…Electronic mail: rgrubio@quim.ucm.es. Similarly, Gavranovic et al, 15 have reported the behavior of dilational viscosity for different polymers, and found that for dilute monolayers the viscosity did not depend on M w , while for more concentrated monolayers there was a linear dependence. In effect, the exponents of the power laws assumed for describing the composition dependence of elasticity and viscosity rely on the following dependence of the relaxation time upon the chain length (N): τ ∼ N 3 .…”
Section: Introductionmentioning
confidence: 75%
“…[158] Among the obtained values there were some, which fell within the range of 0.77-0.79. These values were assigned to polymer chains with statistics of two-dimensional SAW and corresponding critical scaling exponent n ¼ 3/4.…”
Section: Exponent N As a Convenient Quantitative Indicator Of The Conmentioning
confidence: 86%